MEMAKNAI â€œKENDURENâ€ SECARA KRISTIANI DALAM PERSPEKTIF FILSAFAT SIMBOL - Januharka, Markus (Jurnal Orientasi Baru, 2017)
Human beings live in a tension between the need to preserve precious traditions and to discover new values. Javanese people who live the tradition of kenduren for generations look for a new value to live in a new environment of life. Most research on the tradition of kenduren elaborates methods based on interpretation of the local community. This study will make use of Â semantic analysis to interpret kenduren tradition based on philosophy of symbol introduced by Ferdinand de Saussure and Roland Barthes. The purpose of this study is to find new values of the tradition of kenduren. Then, the result of the research shall become a starting point to develop a theological reflection in the perspective of Christian faith as well asto formulate a pastoral program for the people who value and live this respective tradition of kenduren.